Crafting effective engineering problems for problem-based learning: Universiti Teknologi Malaysia experiences - Abd. Hamid, Mohd. Kamaruddin; Abu Hassan, Mohd. Ariffin; Mohd. Yusof, Khairiyah; Syed Hassan, Syed Ahmad Helmi (2005)
In Problem-Based Learning (PBL), complex, real-world and ill-structured problems are used to motivate students to identify and research the concepts and principles they need to work through those problems. It is the key point to implement a successful PBL instruction. However, crafting a good PBL problem is a challenge for instructors in most disciplines including engineering. Typical problems do not foster the development of effective problem-solving and analytical skills nor do they challenge students to develop critical thinking skills and logical reasoning. With the exception of a few disciplines, good PBL problems usually do not appear in textbooks. As a consequence, an instructor needs to create or find problems, modify textbook problems, or write new problems that address the course objectives and learning outcomes. Crafting quality problems are very important for the full benefits of PBL to be realized. Due to instructors’ own learning in the traditional education curriculum, most instructors tend to craft problem based on their subject expertise. This violates the multi-disciplinary richness that PBL advocates. Being able to craft quality and good problem becomes a critical skill for instructors in PBL. This paper aims to describe how to craft effective engineering problems for PBL based on our experiences implementing PBL in Universiti Teknologi Malaysia.